Inner retinal inhibition shapes the receptive field of retinal ganglion cells in primate. (23rd October 2013) - Protti, D. A.; Di Marco, S.; Huang, J. Y.; Vonhoff, C. R.; Nguyen, V.; Solomon, S. G.
Key points: The receptive field of most retinal ganglion cells consists of an excitatory centre and an inhibitory surround. In retinal ganglion cells of non‐primates the receptive field surround is provided by lateral inhibition in both the outer and the inner retinal synaptic layers. We use whole cell recording methods to establish the spatial organisation of excitatory and inhibitory synaptic inputs onto ganglion cells in primate retina. We confirm centre–surround organisation in the excitatory inputs to ganglion cells, and show further that inhibitory inputs can also show centre–surround organisation. We show that lateral inhibition in the inner retina shapes the spatial profile of both excitatory and inhibitory synaptic inputs onto ganglion cells. Dynamic clamp experiments provide evidence that reduction of inner retinal inhibition reduces spatial tuning in ganglion cell output. These results show that lateral inhibition in the inner retina of primate shapes the analysis of spatial form and contrast. Abstract The centre–surround organisation of receptive fields is a feature of most retinal ganglion cells (RGCs) and is critical for spatial discrimination and contrast detection. Although lateral inhibitory processes are known to be important in generating the receptive field surround, the contribution of each of the two synaptic layers in the primate retina remains unclear. Here we studied the spatial organisation of excitatory and inhibitory synaptic inputs onto ON and OFF ganglion cells in the primate retina. All RGCs showed an increase in excitation in response to stimulus of preferred polarity. Inhibition onto RGCs comprised two types of responses to preferred polarity: some RGCs showed an increase in inhibition whilst others showed removal of tonic inhibition. Excitatory inputs were strongly spatially tuned but inhibitory inputs showed more variable organisation: in some neurons they were as strongly tuned as excitation, and in others inhibitory inputs showed no spatial tuning. We targeted one source of inner retinal inhibition by functionally ablating spiking amacrine cells with bath application of tetrodotoxin (TTX). TTX significantly reduced the spatial tuning of excitatory inputs. In addition, TTX reduced inhibition onto those RGCs where a stimulus of preferred polarity increased inhibition. Reconstruction of the spatial tuning properties by somatic injection of excitatory and inhibitory synaptic conductances verified that TTX‐mediated inhibition onto bipolar cells increases the strength of the surround in RGC spiking output. These results indicate that in the primate retina inhibitory mechanisms in the inner plexiform layer sharpen the spatial tuning of ganglion cells.